Exploring the Therapeutic Effects of Noninvasive Brain Stimulation on Motor Function, Cognition, and Quality of Life in Parkinson's Disease: A Systematic Review - Alokaily, Ahmad O. (British Journal of Healthcare and Medical Research, 2024)
Background: Parkinson's Disease (PD) significantly impacts both cognition and quality of life, posing a substantial burden on patients and healthcare systems. However, there is hope on the horizon. Noninvasive brain stimulation (NIBS) has emerged as a potential therapeutic intervention with the power to mitigate these effects. While the evidence regarding its efficacy remains fragmented, the potential it holds is promising. Objective: The present review explores the effects of noninvasive brain stimulation on cognition and quality of life in patients with Parkinson's disease (PD). Methods: A comprehensive search was carried out in electronic databases to find pertinent articles on noninvasive brain stimulation, such as Transcranial direct stimulation (tDCS) and Transcranial Magnetic Stimulation (TMS), in patients with PD. The methodological quality of the included studies was checked using the PEDro scale. Results: A total of 11 studies were finally included in the studies published between 2012 and 2023. Results indicated that a complex relationship exists between cognition and noninvasive brain stimulation. Additionally, possible therapeutic benefits apart from cognition were identified when examining the quality of life in patients with PD. Conclusion: The present review highlights the complex relationship between quality of life and cognitive functioning. In addition, it summarizes the studies performed on noninvasive brain stimulation in PD. These therapies also proved potent in improving general well-being and cognitive domains. More research is needed to determine the best procedures and interventions with suitable therapeutic outcomes.